NEW TRENDS IN STEEL CORD DEVELOPMENT - A. V. Vedeneev (Литьë и металлургия)
The analysis of directions of metal cord constructions developments depending on the place of application in tires of different function is carried out. the requirements to metal cord, which are necessary to be taken into account at development of its new type, are given. the peculiarities of perspective types of reinforcing agents for tires, and also advantages of new types of metal cord over the existing ones are shown.